2020
DOI: 10.1002/bjs5.50298
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic techniques for oesophagectomy for malignancy: systematic review and network meta-analysis

Abstract: Background: Current evidence on the benefits of different anastomotic techniques (hand-sewn (HS), circular stapled (CS), triangulating stapled (TS) or linear stapled/semimechanical (LSSM) techniques) after oesophagectomy is conflicting. The aim of this study was to evaluate the evidence for the techniques for oesophagogastric anastomosis and their impact on perioperative outcomes. Methods: This was a systematic review and network meta-analysis. PubMed, EMBASE and Cochrane Library databases were searched system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…In open esophagectomy, data concludes that stapling techniques seem to be associated with lower rates of anastomotic leakage in comparison to hand-sewn anastomoses. This was shown in a metanalysis by Kamarajah et al in 2020 which included mostly open esophagectomy and very few trials investigating MIE and robotic-assisted minimally invasive esophagectomy (RAMIE) [ 7 ]. Therefore, analyses towards minimally invasive surgery are still pending.…”
Section: Introductionmentioning
confidence: 99%
“…In open esophagectomy, data concludes that stapling techniques seem to be associated with lower rates of anastomotic leakage in comparison to hand-sewn anastomoses. This was shown in a metanalysis by Kamarajah et al in 2020 which included mostly open esophagectomy and very few trials investigating MIE and robotic-assisted minimally invasive esophagectomy (RAMIE) [ 7 ]. Therefore, analyses towards minimally invasive surgery are still pending.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, all studies comparing different surgical techniques for GJ come from bariatric surgery. Recent meta-analyses of various types of esophagogastric anastomosis have shown that LSA is superior with regard to anastomotic leak and stricture rates 34…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses of various types of esophagogastric anastomosis have shown that LSA is superior with regard to anastomotic leak and stricture rates. 34 Primary bariatric surgery is a totally laparoscopic field without inflamed or neoplastic tissues; therefore, unbiased evidences can be provided.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have included both randomized and non-randomized trials, and have found no significant differences in anastomotic leak rates between the two anastomotic techniques (52)(53)(54). A network meta-analysis conducted by Kamarajah (55) demonstrated that stapled anastomosis, including circularand linear-stapled, are associated with lower anastomotic leak rates compared with hand-sewn anastomosis following esophagectomy. Moreover, linear-stapled anastomosis is associated with a lower rate of anastomotic stricture compared with hand-sewn anastomosis.…”
Section: Anastomosismentioning
confidence: 99%